2023
DOI: 10.1002/vnl.21991
|View full text |Cite
|
Sign up to set email alerts
|

A novel phytic acid based flame retardant to improve flame retardancy, hydrophobicity and mechanical properties of linear low‐density polyethylene

Abstract: Exploiting high phosphorus content of phytic acid, it was grafted onto magnesium hydroxide (MH) by neutralization reaction to obtain MGPA, a flame retardant. A current study investigated the effect of MGPA on hydrophobicity, flame retardancy, and mechanical properties of MGPA-linear lowdensity polyethylene (LLDPE) composites. The LLDPE composite with 50 parts of MGPA has the better flame retardancy and thermal stability with a limiting oxygen index of 23.3%, which is higher than that of neat LLDPE (17%). In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Moreover, some studies have found that PA also has a certain promoting effect on the thermal insulation performance of biomass aerogels. The addition of PA can increase the porosity and pore size distribution of the aerogel, improve the pore structure of the aerogel, thereby reducing heat conduction and convection, and enhancing the thermal insulation performance of the aerogel 21,26,27 . In summary, PA demonstrates promising application potential in the research of thermal insulation and flame retardancy of biomass aerogels.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, some studies have found that PA also has a certain promoting effect on the thermal insulation performance of biomass aerogels. The addition of PA can increase the porosity and pore size distribution of the aerogel, improve the pore structure of the aerogel, thereby reducing heat conduction and convection, and enhancing the thermal insulation performance of the aerogel 21,26,27 . In summary, PA demonstrates promising application potential in the research of thermal insulation and flame retardancy of biomass aerogels.…”
Section: Introductionmentioning
confidence: 97%
“…Phytic acid, as a natural organic acid, has attracted extensive attention in the research of thermal insulation and flame retardancy of biomass aerogels in recent years. Phytic acid possesses multiple phosphate groups, which can form a layered structure in the aerogel, effectively preventing the spread of flames and improving the flame retardant performance of the aerogel 21 . Gao et al 22 prepared a new bio‐based phytate PHYPI by performing the salt formation reaction of phytic acid (PA) and piperazine, which showed good flame‐retardant effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the superhydrophilicity of LDHs results in agglomeration and poor distribution in polymer matrices, reducing the mechanical properties of the materials. [14][15][16] In the past decade, various approaches have been implemented to improve the dispersion of LDHs, including surface chemical modification, interlayer intercalation, and exfoliation of LDHs. Among these methods, surface decoration or modification with organic anions can significantly improve the dispersion of LDH nanoparticles within polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…However, LDHs are difficult to delaminate because of the high charge density of the layers and anion content. Moreover, the superhydrophilicity of LDHs results in agglomeration and poor distribution in polymer matrices, reducing the mechanical properties of the materials 14–16 …”
Section: Introductionmentioning
confidence: 99%